Synthesis of a hierarchically porous niobium phosphate monolith by a sol–gel method for fructose dehydration to 5-hydroxymethylfurfural. Issue 14 (4th July 2018) - Gao, Da-Ming; Zhao, Bohan; Liu, Haichao; Morisato, Kei; Kanamori, Kazuyoshi; He, Zhiyong; Zeng, Maomao; Wu, Huaping; Chen, Jie; Nakanishi, Kazuki
Abstract : A new type of niobium phosphate (NbP) with a hierarchically porous structure was synthesised via a sol–gel method accompanied by phase separation and effectively acted as a solid acid for fructose dehydration to HMF. Abstract : Hierarchically porous niobium phosphate (NbP) was synthesised via a sol–gel method accompanied by phase separation and employed as a catalyst for fructose dehydration. The niobium precursor was prepared by digesting ammonium niobate(v ) oxalate in aqueous H2 O2 with citric acid as a chelating agent to prevent the precipitation of niobium hydroxide. Poly(acrylamide) and poly(ethylene glycol) were used as phase separation inducers to produce co-continuous macropores and gel skeletons. The NbP sample calcined at 600 °C for 8 h had a high surface area ( S BET ∼140 m 2 g −1 ) and large acidity (0.84 mmol-NH3 g −1 ). The NbP monolith was amorphous after calcination at 600 °C and transformed into an α-NbOPO4 phase at 1000 °C. The NbP monolith calcined at 600 °C was an efficient acid catalyst for the dehydration of fructose to 5-hydroxymethylfurfural in water (70% yield) or in aqueous dimethyl sulfoxide (90% yield). The productivity of HMF reached 7.3 × 10 −2 mol h −1 per kg-solution at an initial fructose concentration of 10.0 wt% in water with a catalyst loading of 2.0 wt%.